A single black ulcer in a child with acute lymphocytic leukemia - Michelangelo Vestita; Angela Filoni; Nicola Santoro; Gianpaolo Arcamone; Domenico Bonamonte (Sociedade Brasileira de Dermatologia, 2016)
Abstract Ecthyma gangrenosum is an uncommon dermatological manifestation characterized by round, indurated ulcers with a central necrotic black eschar and surrounding erythema. This report describes the case of a 5-year-old girl, affected by acute lymphocytic leukemia, presenting with a black eschar on her right thigh. Such lesions should always be correctly identified to avoid potentially fatal bacteraemia. Furthermore, because of its similar clinical presentation, cutaneous anthrax must be ruled out.